Future places of business in Turku city center : adaptive cycle analysis and Futures Workshop - Eronen, Kirsi (My University, 2020)
Cities are economic hubs, places for enjoyment, social events, culture and consumerism. However, contemporary cities are difficult to understand, and picturing their long-term futures is challenging mainly due to the complex and diverse nature of the city as a whole. The aim of this Master’s thesis is to study the long-term future (up to year 2050) of places of business in Turku city center. The particular study cases are the market square and its surroundings and a pedestrian shopping street, typical spaces which can be found from numerous other city centers as well. These case studies are researched in the context of complexity theories using two analytical methods, one from complexity theories and one from futures studies. The first method is the adaptive cycle analysis which was conducted as a desktop study. The purpose was to find information related to the past and the present phases of the case studies. The second method was a Futures Workshop which was conducted as a participatory expert workshop. The reason for combining the theories of complexity and the analytical methods of the adaptive cycle and the Futures Workshop, was to form a new participatory and transdisciplinary method for studying urban fragments, such as the places of business. This research produced a number of key findings: from the perspective of the analysis of adaptive cycles the marketplace and its surroundings is at the release phase of the current adaptive cycle phase. The pedestrian shopping street is at the conservation phase. The main conclusions drawn from the futures workshop concerning how to be succeed in the future are: widening the use of the market square and at the same time expanding the timeframe of use and making the area more attractive and accessible for citizens by creating better connections between the surrounding buildings and the market square, by planting trees and restricting automobile traffic in the area. For the pedestrian shopping street the suggested measures are: an inclusive and attractive place for every citizen and the sold goods and services as well as the places of business are flexible and work in cooperation so they can adapt to changes in consumer habits. This research has utilized complexity theories using qualitative methods, rather than applied quantitative methods, and has combined two different analytical methods from different disciplines in order to contribute to the study of cities. This study, with complexity theories in the urban context as well as futures studies, has taken a step towards fostering better understanding of the characteristics of successful places of business in the future.

Kaupungit ovat talouden, palvelujen, elämysten, sosiaalisten tapahtumien, kulttuurin ja kuluttamisen keskittymiä. Kaupungin kokonaisuuden ymmärtäminen ja pitkän aikavälin tulevaisuuden hahmottaminen on haasteellista. Suurelta osin tämä johtuu kaupunkien kompleksisuudesta ja monimuotoisuudesta. Tämän Pro gradu -tutkielman tarkoituksena on tutkia Turun kaupungin keskustan liikepaikkojen pitkän aikavälin tulevaisuutta (vuoteen 2050 asti). Erityisinä tutkimuskohteina on kaksi liikepaikkojen keskittymää, tori ja sen ympäristö sekä kävelykatu. Nämä ideaalityypit on löydettävissä myös monien muiden kaupunkien keskustoista. Näitä kahta tutkimuskohdetta tutkittiin kompleksisuusteoreettisesta näkökulmasta käyttäen apuna kahta eri metodia. Ensimmäinen metodi oli kompleksisuusteoriaan perustuva adaptive cycle analysis (kiertokulun analyysi), jota käytettiin menneisyyden ja nykytilan analysointiin. Toisena metodina käytettiin tulevaisuuden tutkimuksen metodia, tulevaisuusverstas. Tulevaisuusverstas toteutettiin asiantuntijatyöpajana. Näiden kahden eri metodin yhdistelmänä oli tarkoitus luoda uusi kvalitatiivinen, osallistava ja poikkitieteellinen tapa tutkia kaupunkikontekstissa esiintyviä kokonaisuuksia (urban fragment), kuten liikepaikkojen keskittymiä. Tämä tutkielma tuotti monenlaisia tuloksia: menneisyyden ja nykytilan analyysin mukaan tori ja sen ympäristö on luovan tuhon vaiheessa (release) ja kävelykatu on kypsyysvaiheessa. Pääkohdat tulevaisuuden menestyvät liikepaikat -työpajasta olivat: torin käyttöä pitää laajentaa monimuotoisemmaksi ja samalla myös sen aikajännettä ja ympärivuotista käyttöä tulee lisätä. Torista ja sen ympäristöstä pitää tehdä mielenkiintoisempi ja helposti saavutettava kokonaisuutena, esimerkiksi lisäämällä vehreyttä ja rajoittamalla autoliikennettä sekä parantamalla alueen rakennusten yhteyttä toriin. Kävelykadun osalta pidettiin tärkeänä inklusiivisuutta ja vetovoimaisuutta kaikkien ikäluokkien näkökulmasta. Myytävien tavaroiden ja palvelujen sekä kiinteistöjen näkökulmasta joustavuus ja yhteistyö nähtiin tärkeinä elementteinä muuttuviin kulutustapoihin sopeutumisessa. Tämä tutkielma tuotti monia vastauksia tulevaisuuden menestyvien liikepaikkojen ominaisuuksiin liittyen, hyödyntäen siihen kompleksisuusteoriaa, tulevaisuuden tutkimusta ja erityisesti niiden kahta kvalitatiivista metodia.
Keywords: futures workshop, adaptive cycle, place of business, futures studies, complexity, urban development, Turku city